2021
DOI: 10.1007/s10461-021-03474-8
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Motherhood and HIV in South Africa: Examining Prevalence of Common Mental Disorder

Abstract: The mental health of adolescents (10–19 years) remains an overlooked global health issue, particularly within the context of syndemic conditions such as HIV and pregnancy. Rates of pregnancy and HIV among adolescents within South Africa are some of the highest in the world. Experiencing pregnancy and living with HIV during adolescence have both been found to be associated with poor mental health within separate explorations. Yet, examinations of mental health among adolescents living with HIV who have experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 77 publications
3
21
0
Order By: Relevance
“…Results show high rates of IPV and pregnancy‐related stigma, both independently associated with higher levels of depression and anxiety, coinciding with previous reports from Uganda and elsewhere in Sub‐Saharan Africa (Atuyambe et al, 2009; Choi et al, 2015; Hall et al, 2018; Ochen et al, 2019; Roberts et al, 2021). Frequently, adolescents who become pregnant out of wedlock in this region face severe social consequences, including social isolation, lack of family, and partner support (Apolot et al, 2020), being forced to leave school (Maly et al, 2017), and being forcibly removed from their homes (Osok et al, 2018), possibly contributing to depression and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Results show high rates of IPV and pregnancy‐related stigma, both independently associated with higher levels of depression and anxiety, coinciding with previous reports from Uganda and elsewhere in Sub‐Saharan Africa (Atuyambe et al, 2009; Choi et al, 2015; Hall et al, 2018; Ochen et al, 2019; Roberts et al, 2021). Frequently, adolescents who become pregnant out of wedlock in this region face severe social consequences, including social isolation, lack of family, and partner support (Apolot et al, 2020), being forced to leave school (Maly et al, 2017), and being forcibly removed from their homes (Osok et al, 2018), possibly contributing to depression and anxiety symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…This previous study of 723 adolescents undertaken within South Africa identified elevated prevalence of common mental disorder among adolescent mothers living with HIV compared to adolescent non-mothers and adolescent mothers not living with HIV. Results from the current study additionally support some of the nuanced findings of this previous study identifying elevated depressive and suicidality symptomology among adolescent mothers living with HIV [ 21 ]. Potentially reflecting the myriad of challenges, and the ongoing need for support, experienced by adolescent mothers in this setting, particularly those living with HIV [ 21 ].…”
Section: Discussionsupporting
confidence: 86%
“…if a participant scored above the cut-off on any of the four mental health measures within the study (see below) they were classified as experiencing poor mental health and, 2) Any likely mental health comorbidities (MHCs); i.e. if a participant scored above the cut-off on two or more of the mental health measures within the study (see below) they were classified as experiencing mental health comorbidities [ 36 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations